Assessing the Acceptance of Blended Learning Implementation in Universitas Lancang Kuning using the Technology Acceptance Model - Novendra, Rizki; Ambiyar, Ambiyar; Fadhilah, Fadhilah; Syahril, Syahril; Sutejo, Sutejo; Fadrial, Yogi Ersan (FKIP Universitas Lampung, 2021)
The Covid-19 pandemic has forced learning activities to be carried out online. In response to this, Universitas Lancang Kuning, which has implemented the Blended Learning application, wants to measure the level of use and understand the factors that influence the acceptance of the system in an agency. The study was conducted at the Unilak Fasilkom with 92 samples. Data obtained by distributing questionnaires based on indicators and variables of the technology acceptance modelling method. The results of this study indicate that the multiple regression analysis of the variables that have an influence on the real condition of information users is the variable Benefits of using information systems (X1), User Ease of Information Systems (X2), and User Attitudes towards Information Systems (X3) have a significant influence on real condition of information system users (Y). Meanwhile, the behavior of information system users (X4) has no effect.Keywords: technology acceptance model, blended learning, covid-19 pandemic. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp198-205